1995
DOI: 10.1073/pnas.92.15.7105
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mitochondrial energy impairment produces selective striatal degeneration and abnormal choreiform movements in primates.

Abstract: Although the gene defect responsible for Huntington disease (HD) has recently been identified, the pathogenesis of the disease remains obscure. One potential mechanism is that the gene defect may lead to an impairment of energy metabolism followed by slow excitotoxic neuronal injury. In the present study we examined whether chronic administration of 3-nitropropionic acid (3-NP), an irreversible inhibitor of succinate dehydrogenase, can replicate the neuropathologic and clinical features of HD in nonhuman prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
240
0
4

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(257 citation statements)
references
References 30 publications
13
240
0
4
Order By: Relevance
“…4). In concert with previous studies demonstrating defective mitochondrial function in HD patients and transgenic mice (19,(22)(23)(24), our findings suggest that loss of mitochondrial CREB may play a role in the pathophysiology of HD. Table 1 and Fig.…”
Section: Resultssupporting
confidence: 66%
“…4). In concert with previous studies demonstrating defective mitochondrial function in HD patients and transgenic mice (19,(22)(23)(24), our findings suggest that loss of mitochondrial CREB may play a role in the pathophysiology of HD. Table 1 and Fig.…”
Section: Resultssupporting
confidence: 66%
“…Furthermore, we recently demonstrated that creatine administration can block 3-NP-induced decreases in both phosphocreatine and ATP and exert significant neuroprotection, consistent with an effect of 3-NP on energy metabolism (Matthews et al, 1998). Following administration of 3-NP to primates, there is selective neuronal degeneration, as well as an apomorphine-inducible choreiform movement disorder that strongly mimics that seen in HD (Brouillet et al, 1995).…”
Section: Resultsmentioning
confidence: 88%
“…The finding that the HD transgenic mice show increased sensitivity to 3-NP is of interest, because 3-NP administration replicates many of the neurochemical and neuropathologic findings of HD (Beal et al, 1993;Brouillet et al, 1995). Accidental ingestion of 3-NP in humans results in selective basal ganglia lesions accompanied by delayed onset of chorea and dystonia (Ludolph et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter possibility seems less likely in view of the toxicity of polyglutamine in COS cells [13] and in E. coli. A potential mechanism of toxicity is a quantitative or qualitative change in protein-polyglutamine domain interactions which vary as a function of polyglutamine length [30]. Polyglutamine domains can mediate protein-protein interactions by forming polar zippers.…”
Section: Discussionmentioning
confidence: 99%